Hubungan Sikap, Jarak Tempuh, Dan Dukungan Keluarga Pada Ibu Hamil Trimester 3 Terhadap Kepatuhan Ibu Hamil Untuk ANC Tahun 2022: Correlation between Attitude, Mileage, and Family Support in Trimester 3 Pregnant Women to Compliance of Pregnant Women for ANC in 2022 - Meilani, Dini (Dohara POAJ, 2023)
Introduction: ANC compliance is the obedience to visit health care facilities by pregnant women according to the advice of health workers. The consequences and impacts that might occur if you don't go on a pregnancy visit are that the mother can't find out about fetal development, increases MMR and IMR, and doesn't know what precautions to take if complications occur in pregnancy. Factors that influence ANC compliance are attitude, mileage, and family support. Efforts that can be made to increase compliance with ANC visits are midwives providing education and approaches to the community and cadres reminding mothers to check their pregnancies. Methods: This study used a descriptive-analytic with a cross-sectional approach. The sampling technique used was simple random sampling with a sample size of 42 people. Results: The results showed that there was a significant relationship between attitude and ANC compliance with a p-value of 0,000; distance traveled with ANC compliance obtained a p-value of 0,005; family support with ANC compliance obtained a p-value of 0,000. Discussion: The conclusion of this study is that there is a relationship between attitudes, mileage, and family support with ANC compliance at PMB Midwife Deis Bogor Regency in 2022. Suggestions for pregnant women to carry out routine pregnancy checks in order to monitor the health and welfare of the fetus in the womb.